Teaching good behaviour (Time-Life Books Hong Kong, 2000)
is a practical guide for parents and educators on fostering positive behavior in children through a structured and developmental approach. The book outlines the stages of childhood development, offering tailored strategies for teaching good manners, respect, and self-discipline at each age. By following a timeline, it helps caregivers introduce appropriate behavioral lessons at the right times, encouraging consistency and patience. The book emphasizes the importance of understanding a child's needs and capabilities at different stages, making the process of teaching good behavior both effective and rewarding.